Quantitative analysis of astrocyte and axonal density relationships: Glia to neuron ratio in the optic nerve laminar regions. (September 2020) - Chan, Geoffrey; Morgan, William H.; Yu, Dao-Yi; Balaratnasingam, Chandrakumar
Abstract: Astrocytes are critical for the maintenance of retinal ganglion cell (RGC) axonal function and viability, and form a key component of the functional neurovascular unit. Recently, we described the quantitative properties of astrocytes in relation to the capillary distributions in optic nerve laminar regions. Here, we provide a quantitative analysis of astrocytes and RGC axons in longitudinal sections of optic nerve tissue. Histological and immunocytochemical techniques are used to demonstrate the density of astrocytes, RGC axons and glia-neuron ratios across the pre laminar, lamina cribrosa and post laminar compartments of the optic nerve head (ONH). A study of human, pig, horse and rat optic nerves was performed and comparisons are made between species. This study demonstrates that the distribution of astrocytes correlates closely with the density of axonal processes, in accordance with the functional requirement of different regions of the ganglion cell axon. There was a consistency of glia-neuron ratios in the majority of laminar compartments, except for the human and rat prelaminar regions, which demonstrated lower ratios of astrocyte to axonal processes. The distribution of astrocytes may reflect a functional susceptibility to development of disease in the prelaminar region of the optic nerve. Interspecies comparison at the lamina cribrosa showed strikingly consistent glia-neuron ratios. Collectively, our findings suggest there may be a critical ratio of glia to neuron needed to maintain healthy cellular physiology across different laminar compartments of the optic nerve, with particular importance for the health of the lamina cribrosa region. It is possible that, in disease processes, the glia-neuron relationships across the different laminar compartments may be perturbed and this may be relevant for the development of glaucoma. Emerging technologies may further aid our understanding in how the physiology of optic nerve tissue cellular structure may be affected by changes to ONH characteristics and elevated intraocular pressure induced damage. Such findings may also permit the early identification of RGC axonal injury by identifying quantifiable changes in structural tissue architecture when pathophysiological pathways predominate. Highlights: Glia-neuron ratios were uniform across the majority of laminar compartments for all animal species studied. Interspecies comparison at the lamina cribrosa yielded strikingly consistent glia-neuron ratios. The density of astrocytes correlate with the density of axonal processes, in accordance with functional requirements.